Analisis aliran fluida pada sepeda motor x saat berkendara di jalan tol menggunakan metode CFD - Varhani, Ferry; Luthfie, Alief Avicenna (Journal of New Energies and Manufacturing, 2022)
Motorcycles are the most common form of transportation in Indonesia. Motorcycles can only drive on non-toll roads according to Indonesian law. In 2019 there was a discourse from the government that allowed motorcycles to enter toll roads. However, vehicles such as motorcycles have serious problems with the wind loads they receive. Besides the damaged road surface, the wind is a problem for motorcyclists. On toll roads that have at least 2 lanes per direction, it is possible for a vehicle to receive a fluid distribution from other vehicles next to it. With a constant speed of 60 km/hour on a motorcycle and a speed of 60,90 and 120 km/hour on a car, the simulations form positions A, B, and C.